A 2in1 cloning system enables ratiometric bimolecular fluorescence complementation (rBiFC). (November 2012) - Grefen, Christopher; Blatt, Michael R.
Gene expression and binary interaction techniques are vital tools that shape our understanding of protein complexes. An inherent flaw, however, with most current protein-protein interaction techniques is the variability in expression levels for fusion proteins when using several individual plasmids. Here, we describe a novel recombination-based cloning strategy called 2in1 that enables co-expression of fusion proteins on a cell-by-cell basis from a single plasmid. We demonstrate the utility of 2in1 through the development of a ratiometric bimolecular fluorescence complementation assay (rBiFC), in which both candidate genes are simultaneously cloned into a single vector backbone containing an internal fluorescent marker for expression control and ratiometric analysis. rBiFC significantly increases the credibility of protein-protein interaction results allowing ratiometric comparison between different protein pairs. In addition to its use in rBiFC, 2in1 can be introduced easily into other vector systems that rely on multiple gene expression and prove feasible in future synthetic biological approaches.